2021
DOI: 10.3390/ijms22168609
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2-(Adamantan-1-ylamino)Thiazol-4(5H)-One Derivatives and Their Inhibitory Activity towards 11β-HSD1—Synthesis, Molecular Docking and In Vitro Studies

Abstract: A common mechanism in which glucocorticoids participate is suggested in the pathogenesis of such metabolic diseases as obesity, metabolic syndrome, or Cushing’s syndrome. The enzyme involved in the control of the availability of cortisol, the active form of the glucocorticoid for the glucocorticoid receptor, is 11β-HSD1. Inhibition of 11β-HSD1 activity may bring beneficial results for the alleviation of the course of metabolic diseases such as metabolic syndrome, Cushing’s syndrome or type 2 diabetes. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The studies were conducted using liver microsomes. The obtained results support the participation of GCs in the pathogenesis of such metabolic diseases as obesity, metabolic syndrome, or Cushing’s syndrome [ 101 ].…”
Section: 11β-hsd1 Inhibitors In the Therapy Of Components Of The Meta...supporting
confidence: 72%
“…The studies were conducted using liver microsomes. The obtained results support the participation of GCs in the pathogenesis of such metabolic diseases as obesity, metabolic syndrome, or Cushing’s syndrome [ 101 ].…”
Section: 11β-hsd1 Inhibitors In the Therapy Of Components Of The Meta...supporting
confidence: 72%
“…The biological activity of a compound depends on its chemical structure, hence structural fragments characteristic for inhibitors that have reached the stage of clinical trials are observed in the new tested compounds. In vitro studies were carried out for various structures, of which the group of compounds containing a thiazole ring [ 117 , 133 , 134 , 135 ] or its partially hydrogenated form, thiazol-4-one [ 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ], seems to be the most numerous and promising ( Figure 5 ). Compounds containing fused systems with a thiazole ring [ 144 , 145 ] and other various heterocyclic systems with nitrogen atoms [ 146 , 147 , 148 , 149 , 150 , 151 , 152 ] were also analyzed as potential selective inhibitors of 11β-HSD1 ( Figure 6 ).…”
Section: Examples Of Selective 11β-hsd1 Inhibitors As Potential Drugs...mentioning
confidence: 99%
“…For example cyclic sulfonamides are highly selective inhibitors [ 154 , 155 , 156 , 157 ]. In many tested compounds with high activity and selectivity, the adamantyl substituent [ 139 , 146 , 149 , 150 , 151 , 153 , 154 , 156 ] and other polycyclic condensed systems [ 142 , 158 , 159 ] as well as halo-substituted phenyl rings [ 133 , 136 , 143 , 154 , 160 ] are constituents of the structure ( Figure 6 ).…”
Section: Examples Of Selective 11β-hsd1 Inhibitors As Potential Drugs...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the desadamantyl 1,2,4-triazole derivatives IV [21], V [22] and VI [23], are currently under clinical investigations as 11β-HSD1 inhibitors for the treatment of type 2 diabetes and obesity (Figure 1). According to experimental and molecular docking studies for the identification of chemical features of 11β-HSD1 inhibitors, a combination of an adamantane cage-and 1,2,4-triazole or other azole moieties could result in potent 11β-HSD1 inhibitors [15,16,[24][25][26][27][28][29]. In continuation with ongoing interest in the structural properties [30][31][32][33][34][35] and biological applications of adamantane-based derivatives [35][36][37][38][39], we report herein on the molecular structure insights, Hirshfeld surface analysis and pairwise interaction energies of three adamantane-linked 1,2,4-triazole N-Mannich bases, namely ethyl 4-[(3adamantan-1-yl)-4-ethyl-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-1-yl)methyl]piperazine-1carboxylate (1), 5-(adamantan-1-yl)-4-ethyl-2-[(4-(pyridin-2-yl)piperazin-1-yl)methyl]-2,4-dihydro-3H-1,2,4-triazole-3-thione (2) and 5-(adamantan-1-yl)-4-allyl-2-[(4-(pyridin-2yl)piperazin-1-yl)methyl]-2,4-dihydro-3H-1,2,4-triazole-3-thione (3), which were proven to possess marked hypoglycemic activity [39].…”
Section: Introductionmentioning
confidence: 99%